Effect of renal denervation on blood biomarker levels in patients with resistant hypertension, diabetes and coronary artery disease after 12-month follow-up - N. A. Arablinsky; D. A. Feshchenko; V. A. Metelskaya; Yu. S. Timofeev; F. B. Shukurov; M. T. Taliuridze; D. K. Vasiliev; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of catheter renal denervation (RDN) on blood biomarker levels in patients with cardiovascular comorbidity and type 2 diabetes (T2D).Material and methods. Sixty patients with true resistant hypertension (HTN) in combination with T2D and coronary artery disease after complete myocardial revascularization using percutaneous coronary intervention were included in a prospective observational non-randomized study. Patients were distributed in a 1:1 ratio into the intervention group and the control group. RDN was performed through femoral access using a Spyral system (Medtronic, USA). The primary endpoint was the change in plasma renin activity after 12 months. The results are presented as Me (Q25; Q75).Results. In the intervention group, plasma renin activity significantly decreased from 4,65 (1,88; 7,79) to 2,21 (0,87; 5,49) ng/ml/h; angiotensin-I from 1,73 (0,34; 3,22) to 0,46 (0,31; 1,95) ng/ml; aldosterone from 131 (78; 173) to 118 (68; 153) pg/ml (p<0,05 for all). There were no significant changes in the control group. A decrease in office systolic and diastolic blood pressure was confirmed, with the greatest antihypertensive effect achieved in the high-renin hypertension group (renin activity at inclusion >6,5 ng/ml/h). The blood pressure decreases correlated with decrease in plasma renin activity (r=0,85; p<0,05). A significantly positive effect of RDN on reducing the levels of C-reactive protein, fasting glucose, glycated hemoglobin, and triglycerides was revealed (p<0,05 for all), without significant changes in the control group. The intervention and control groups did not statistically differ in the incidence of major adverse cardiovascular events, the glomerular filtration rate was comparable in both groups and did not change over time.Conclusion. The use of RDN in comorbid patients is safe and allows for better control of modifiable risk factors for the progression of HTN and T2D due to an improvement of blood pressure, carbohydrate metabolism parameters, regulatory factors of the renin-angiotensin-aldosterone system, and factors of the systemic inflammatory response.